ANALISIS KESESUAIAN PROGRAM PENGELOLAAN SAMPAH PADA TPS 3R PEDALANGAN BANYUMANIK SEMARANG - Jeff Gracendrei, Giosia; Rostyaningsih, Dewi; Warsono, Hardi (Journal of Public Policy and Management Review, 2024)
Waste management is one of the main challenges faced by cities in developing countries, including Indonesia. This study examines the suitability of waste management policies through TPS 3R Pedalangan Banyumanik Semarang. The research method used is descriptive with a qualitative approach, involving observation, content analysis, and literature study. This research found that the success of the waste management program is influenced by several factors, including continuous socialization and education for the community, providing incentives to active participants, collaboration with educational institutions, as well as participatory monitoring and evaluation. Additionally, adequate infrastructure and active community involvement in every stage of the program are also key to success. The conclusion of this study indicates that appropriate waste management requires active participation from all community elements, government support, and adaptability and flexibility in policy alignment. The suitability of the waste management program at the 3R TPS Pedalangan has not been fully achieved, primarily due to the urgent need to improve socialization, education, coordination among implementers, and community participation so that the program can run more effectively and in accordance with applicable regulations. Based on the research findings, it is necessary to develop continuous socialization and education programs, enhance the capacity and competence of officers through advanced training, and establish community working groups for waste management.